Medical progress, demand for health care, and economic performance - Ivan Frankovic; Michael Kuhn; Stefan Wrzaczek (Vienna University of Technology, Institute of Statistics and Mathematical Methods in Economics, Research Group Economics, 2017)
We study medical progress within an economy of overlapping generations subject to endogenous mortality. Individuals demand health care with a view to lowering mortality over their life-cycle. We characterise the individual optimum and the general equilibrium of the economy and study the impact of improvements in the effectiveness of health care. We find that general equilibrium effects dampen strongly the increase in health care usage following medical innovation. Moreover, an increase in savings offsets the negative impact on GDP per capita of a decline in the support ratio.
Keywords: D91; I11; I12; J11; J17; O31; O41; 330; life-cycle model; longevity; health care; medical innovation; overlapping generations; value of life